Differential Effects of Novel Dopamine Reuptake Inhibitors on Interference With Long-Term Social Memory in Mice - Camats-Perna, Judith; Kalaba, Predrag; Ebner, Karl; Sartori, Simone B.; Vuyyuru, Harish; Aher, Nilima Y.; Dragačević, Vladimir; Singewald, Nicolas; Engelmann, Mario; Lubec, Gert (Frontiers in Behavioral Neuroscience, 2019)
In the laboratory, long-term social recognition memory in mice is highly susceptible to proactive and retroactive interference. Here we investigate the ability of novel designed dopamine re-uptake inhibitors (rac-CE-123 and S-CE-123) to block retroactive and proactive interference respectively. Our data shows that administration of rac-CE-123 30 min before learning blocks retroactive interference that has been experimentally induced at 3 h, but not at 6 h, post learning. In contrast S-CE-123 treatment 30 min before learning blocked the induction of retroactive interference at 6 h, but not 3 h, post learning. Administration of S-CE-123 failed to interfere with proactive interference at both 3 h and 6 h. Analysis of additional behavioral parameters collected during the memory task imply that the effects of the new dopamine re-uptake inhibitors on retroactive and proactive interference cannot easily be explained by non-specific effects on the animals’ general social behavior. Furthermore, we assessed the mechanisms of action of drugs using intracerebral in vivo-microdialysis technique. The results revealed that administration of rac-CE-123 and S-CE-123 dose dependently increased dopamine release within the nucleus accumbens of freely behaving mice. Thus, the data from the present study suggests that the dopamine re-uptake inhibitors tested protect the consolidation of long-term social memory against interference for defined durations after learning. In addition, the data implies that dopamine signaling in distinct brain areas including the nucleus accumbens is involved in the consolidation of social recognition memory in laboratory mice.